Pharmacovigilance of antiretroviral drugs in BPKIHS. - Saraf,Deependra Prasad (2019)
ABSTRACT: Introduction: Antiretroviral therapy (ART) is lifeline for patients living with HIV (PLHIV); however it has been associated with various adverse drug reactions (ADRs). The ADRs are likely to compromise the compliances to ART. With the primary objectives of estimating the prevalence of ADRs of ART, this study was conducted among PLHIV in Eastern Nepal. Materials and Methods: A prospective cohort study was conducted among 496 PLHIV at BPKIHS, Dharan, Nepal for a period of one year. ADRs were evaluated based upon clinical history followed by standard clinical examination and investigations. Descriptive statistics parameters mean, SD, frequency and percentage were calculated for normally-distributed variables. Chisquare test was used for analyzing categorical data and Student's t tests for non-categorical data at P-value < 0.05. All statistical calculations were performed using SPSS version 11.5 (Chicago, USA). Results: Majority of PLHIV (58.1%) were of 31-45 year age group with almost equal gender distribution. Half of the patients (258, 51.5%) were on TDF-3TC-EFV followed by ZDV-3TCEFV (89, 17.8%) and ZDV-3TC-NVP (86, 17.2%). Prevalence of polypharmacy was 2.6%. Immune reconstitution inflammatory syndrome (IRIS) to ART was observed in 16 (3.2%) patients. Total of 240 ADRs were suspected. One hundred and seventy two (34.9%) patients experienced at least one ADR. Skin rash, anemia and nausea and vomiting were top three common ADRs. The ADRs were statistically significant with patients having non-communicable diseases, chronic coinfections, patients on multiple drugs other than ART, second and third line ART regimen. Modification of ART was demanded among 68 (13.7%) PLHIV. Conclusions: One third of patients on ART experienced ADR. NCDs, chronic co-infections and polypharmacy were identified as risk factor for occurrence of ADR among PLHIV with ART. Keywords: Adverse drug reactions; Antiretroviral Therapy; Pharmacovigilance